The early conversion of deep-sea wood falls into chemosynthetic hotspots revealed by in situ monitoring - Kalenitchenko, D. (Sci Rep, 2018)
Wood debris on the ocean floor harbor flourishing communities, which include invertebrate taxa thriving in sulfide-rich habitats belonging to hydrothermal vent and methane seep deep-sea lineages. The formation of sulfidic niches from digested wood material produced by woodborers has been known for a long time, but the temporal dynamics and sulfide ranges encountered on wood falls remains unknown. Here, we show that wood falls are converted into sulfidic hotpots, before the colonization by xylophagaid bivalves. Less than a month after immersion at a depth of 520 m in oxygenated seawater the sulfide concentration increased to millimolar levels inside immersed logs. From in situ experiments combining high-frequency chemical and video monitoring, we document the rapid development of a microbial sulfur biofilm at the surface of wood. These findings highlight the fact that sulfide is initially produced from the labile components of wood and supports chemosynthesis as an early pathway of energy transfer to deep-sea wood colonists, as suggested by recent aquarium studies. The study furthermore reveals that woodborers promote sulfide-oxidation at the periphery of their burrows, thus, not only facilitating the development of sulfidic zones in the surrounding of degraded wood falls, but also governing sulfur-cycling within the wood matrix.